Between External Influence and Autonomy of Schools: Effects of External Evaluation of Schools - Ana Mouraz; Carlinda Leite; Preciosa Fernandes (Paidéia (Ribeirão Preto))
Abstract The article analyzes the relationship between the External Evaluation of Schools (EES) - which takes place in Portugal since 2006 - and the curricular management processes. Its objective is to identify the effects of this evaluation on the curriculum management of schools. Data were collected by 108 questionnaires, two interviews and two focus groups in two Portuguese school groups with two distinct situations: a school group that rose in the rankings from the first to the second evaluation cycle (from 2006-2011/2012 to 2012-2015/2016) and the other one which dropped. The data analysis showed that the EES had a moderate impact on the curricular practices of the school group studied. However, there was a difference: the school group that rose in the rankings recognizes in more aspects and with more clarity the impact of EES on the restructure of its curricular practices.